Perspective of Governance in University Institutions in Virtual Digital Environments - Martínez, Edgar German; Sánchez Vázquez, Elizabeth; Poveda Aguja, Fernando Augusto; Barbosa Guerrero, Lugo Manuel; Cruz Mican, Edgar Olmedo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Study was born in the construction of problem concepts in the deployment of a governance strategy in institutions under digital environments, a technical position of understanding from South America is raised, the initial hypothesis of knowing aspects and determining requirements, an efficient model of governance can be achieved from the use and application of ICT , which allow to argue the as of the process, The use ICT, TAC, TEP as change managers in virtuality, to interact in a disruptive way, the most important achievements of research to recognize the legal, digital and technological resource environment.